Cops: Know Your Rights - Anderson, Jasmine (2015)
Radars beeped, scans ran and the siren was ready for use. Taking the passenger seat in the Iowa State Campus Police car, flashbacks of “Reno 911” episodes ran through my mind as I imagined all of the sweet moves that would be thrown down on every freshman traveling with a backpack full of Keystone. Roaming through Campustown, we drove slowly, circling the mass of students traveling between parties and bar